REPRESENTASI IDENTITAS ANAK DALAM ANIMASI UPIN DAN IPIN MUSIM 10 EPISODE 11 - Hardika, Bara Bima; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this study is to see how the representation and meaning of connotation denotation, and the identity myths of children in the animation Upin and Ipin season 10 episode 11 through the signs that exist in this with the analysis using semiotics analysis Roland Barthes. To collect research data using, documentation, and literature study. The results show the existence of a child's identity is represented as individuals who still want to learn culture in their own country. The form of identity is, fantasize and imagine, have curiosity, spontaneous, learn many things using the body, and have a high learning spirit. This research is also required to see how the form of ideology and what interests are there in this animation, by viewing impressions of Upin and Ipin this includes frequent repetitions. In one case, the impressions of Upin and Ipin have a fairly intensive run, which is three times a day.Keywords : Representation, identity, semiotic, animation